A reformulated hardening soil model. Issue 3 (13th September 2019) - Bower, Thomas A.; Jefferson, Anthony D.; Cleall, Peter J.
Abstract : The hardening soil (HS) model is an advanced soil plasticity model, which incorporates many features including stiffness stress dependency, hardening from initial loading and soil dilatancy. In this paper, the HS model is explored in depth and two improvements are proposed. The first is a new shear yield surface and hardening rule that have been reformulated to remove singularities. The second is a robust implicit return mapping scheme. Options for improving the global convergence of finite-element analyses are also explored. Single-elements tests replicate results from experimental triaxial data and previous versions of the HS model very closely, and at excellent convergence rates. In addition, a slope stability analysis is performed using the φ − c strength reduction method in two-dimensional plane strain. The results from the slope analysis showed good agreement with analytical and graphical slope stability methods. A three-dimensional (3D) slope stability analysis was also conducted with modified boundary conditions, in order to demonstrate the 3D capabilities of the model.